PENINGKATAN PEMAHAMAN KONSEP SAINS MELALUI PENERAPAN METODE DEMONSTRASI PADA SISWA SEKOLAH DASAR - Nurpadila; Sumianto; Fadhilaturrahmi; Fitra Surya, Yenni; Aprinawati, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background to this research is the low ability to understand science concepts of students in class V UPT SD Negeri 011 Sei Jalau. This research aims to improve the ability to understand scientific concepts through the application of the demonstration method in class V UPT SD Negeri 011 Sei Jalau. This research is classroom action research carried out in 2 cycles and each cycle consists of 2 meetings. The subjects in this research were 17 students in class V UPT SD Negeri 011 Sei Jalau, consisting of 10 male students and 7 female students. This research instrument consists of teacher activity observation sheets, student activity observation sheets, test sheets, and documentation sheets. Meanwhile, the data analysis techniques used are qualitative analysis and quantitative analysis. asked on the results of research that was carried out in 2 cycles, in cycle I, meeting 1, there were 8 students (47.1%), in cycle I, meeting 2, there were 10 students (58.8%), in cycle II, meeting 1. there were 12 students (70.6%), and in cycle II meeting 1 there were 14 students (82.4%). This it can be concluded that through the application of the demonstration method it can improve the ability to understand science concepts of class V students at UPT SD Negeri 011 Sei Jalau.